PEMBUATAN PELANCAR ASI BERUPA TEH DAUN KATUK di TPMB MIMIK S, Amd.Keb, KECAMATAN MUMBULSARI KABUPATEN JEMBER - Dinar Perbawati Perbawati (Jurnal SADEWA, 2025)
Breast milk is the natural first food for babies, providing all the energy and nutrients a baby needs for the first months of life (1). According to the World Health Organization (WHO), babies should be given exclusive breastfeeding for at least 6 months and continue to be given until the child is 2 years old (2). This is done with the aim of reducing the number of infant morbidity and mortality (2). Breast milk production is important in the breastfeeding process (2). Improving the quality of foods that can stimulate the release of breast milk, such as green vegetables, katuk leaves, sweet potato leaves, papaya, and so on, is one way to increase breast milk production (7). Katuk leaves contain polyphenols and steroids that play a role in the prolactin reflex or stimulate the alveoli to produce breast milk, and contain sterols with estrogenic properties that stimulate the hormone oxytocin to facilitate the release of breast milk, so katuk leaves are recommended for mothers who have difficulty breastfeeding (8). The purpose of this Community Service Activity is expected to provide knowledge both in theory and practical skills to breastfeeding mothers at PMB Mimik Suwarminingsih, Amd.Keb, and to help mothers who experience difficulties in providing breast milk. The methods used in this community service activity use health promotion, support, and empowerment methods that target pregnant and postpartum women.